THE SPIRITUAL DIMENSION OF HERITAGE BUILDINGS - GREGORY B. WILLSON (Centre For Tourism Planning and Development, 2013)
Traditionally within the developed western world, decisions concerning the preservation of heritage buildings and sites have been primarily based upon economic measurement and criteria. It is recognised that heritage assets offer many experiential qualities and hold importance to the wider lives of individuals; specifically, tourists and host communities imbue the sites with their own personal values and subjective significance. They seek personal meaning and connection through their experiences with heritage. In this way, the accountability of heritage building preservation can be viewed in greater terms than solely their economic value. Despite this recognition, there remains a lack of attention in previous heritage tourism studies towards exploring the personal meaning and experiential qualities of heritage buildings, with the exception of the literature focusing on buildings of religious significance. Further, the spiritual value of heritage has been explored largely within the context of sites of religious significance; spirituality though is a broader, more encompassing concept than religion. This paper explores the spiritual value ascribed by international tourists to heritage buildings within a particular region of New Zealand: Hawke's Bay. Sixty-six photograph-supported interviews conducted with international tourists found that heritage buildings can hold deep 'spiritual' meaning to individuals. Rather than any religious significance, findings showed that heritage buildings render the townscape an experiential 'spiritual' space filled with emotion, mindfulness, engagement and personal meaning. The paper concludes that this finding has important implications for the way in which heritage buildings are promoted, developed and preserved within a destination townscape.